CDKL5 deficiency predisposes neurons to cell death through the deregulation of SMAD3 signaling. (22nd March 2019) - Fuchs, Claudia; Medici, Giorgio; Trazzi, Stefania; Gennaccaro, Laura; Galvani, Giuseppe; Berteotti, Chiara; Ren, Elisa; Loi, Manuela; Ciani, Elisabetta
Abstract: CDKL5 deficiency disorder (CDD) is a rare encephalopathy characterized by early onset epilepsy and severe intellectual disability. CDD is caused by mutations in the X‐linked cyclin‐dependent kinase‐like 5 ( CDKL5 ) gene, a member of a highly conserved family of serine‐threonine kinases. Only a few physiological substrates of CDKL5 are currently known, which hampers the discovery of therapeutic strategies for CDD. Here, we show that SMAD3, a primary mediator of TGF‐β action, is a direct phosphorylation target of CDKL5 and that CDKL5‐dependent phosphorylation promotes SMAD3 protein stability. Importantly, we found that restoration of the SMAD3 signaling through TGF‐β1 treatment normalized defective neuronal survival and maturation in Cdkl5 knockout (KO) neurons. Moreover, we demonstrate that Cdkl5 KO neurons are more vulnerable to neurotoxic/excitotoxic stimuli. In vivo treatment with TGF‐β1 prevents increased NMDA‐induced cell death in hippocampal neurons from Cdkl5 KO mice, suggesting an involvement of the SMAD3 signaling deregulation in the neuronal susceptibility to excitotoxic injury of Cdkl5 KO mice. Our finding reveals a new function for CDKL5 in maintaining neuronal survival that could have important implications for susceptibility to neurodegeneration in patients with CDD.